SPIN SUSCEPTIBILITY IN TWO DIMENSIONS - GROSU, I. (Studia Universitatis Babeș-Bolyai Physica, 2016)
The static spin susceptibility of a two dimensional electron system is calculated, for two distinct situations. The first system is one with a parabolic dispersion law, and the second system is one with a linear dispersion law, corresponding to graphene systems. The temperature dependence of the static spin susceptibility is analyzed up to room temperatures for both systems.